PERSEPSI MASYARAKAT TENTANG NILAI MORAL DALAM ADAT BASIACUANG DI DESA KUMANTAN KECAMATAN BANGKINANG KABUPATEN KAMPAR - Iqbal, Ahmad; Hambali, Hambali; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on customary basiacuang in kampar regency as a custom which become the culture of kampar residents especially kumantan village. So the writer take title research